Development Planning in The “Flood-Free Serang” Program in The City of Serang - Chanila Misya Subkhan; Laeli Nur Khanifah; Rayhan Puta Sasmita; Ezra Kalyla; Rafasha Rafasha (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines development planning within the Flood Free Serang Program in the City of Serang with particular attention to planning processes, stakeholder coordination, and implementation effectiveness. The research employed a qualitative case study approach involving key actors from BBWS C3, the Serang City Government, the Public Works and Spatial Planning Office, the Environmental Agency, and community representatives. Data were collected through semi structured interviews, document analysis, and institutional reports, and were analyzed using an interactive qualitative framework. The findings indicate that development planning was formulated through an integrated perspective that addressed flood causes across river systems, urban infrastructure, environmental management, and community engagement. Collaborative governance emerged as a critical factor supporting policy implementation through coordination among governmental institutions and local stakeholders. The program contributed to reduced flood occurrence in several locations and strengthened institutional capacity for flood management. Challenges persisted in relation to budget constraints, community awareness, land use pressures, and limitations in cross sector collaboration. The study highlights the importance of integrated planning, adaptive governance, and participatory approaches for strengthening urban flood resilience and supporting sustainable development in rapidly growing urban areas.